Animals in anthropology: From objects of ethnography to ethnographic subjects? - Leblan, Vincent; Roustan, Mélanie (Ethnography, 2025)
The paper addresses animals potential as ethnographic subjects. This issue challenges anthropology and its perimeter, by renewing and diversifying the array of understandings of relationships between informants and ethnographers. We first look at how anthropologists draw some boundaries based on how and to what extent they take the inner world of animals into consideration. We then test the observations of ethologists who claim to produce ethnographic knowledge against anthropologists’ reflexivity about their own observational practices. We suggest the affirmation of “animal culture” is not a relevant condition to consider that ethnography can be practised with animals, since “cultural behaviours” in primatology remain interpreted within a biological frame. Thus, we explore two methodological pillars of fieldwork in relation to the possibility of an animal ethnography: the role of observation and the importance of communication with informants. This raises questions about the links between anthropology and ethology, and between ethnocentrism and anthropocentrism.